(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Effects of supplementary feeds on growth, survival, and production of red fin mahseer, Tor tor (Hamilton) was assessed in captive condition under a monoculture system. Experiments were conducted for a period of 12 months where two feeds varying in protein contents were used in treatments. One laboratory formulated feed with 36.67% protein and a commercial feed with 28% protein were characterized as treatment-1 (T1) and treatment-2 (T2), respectively. At the same time water quality parameters were measured. The net increment in weight after 12 months was 671.60 g and 509.80 g in T1 and T2 respectively. The feed conversion ratio (FCR) was 4.72 and 5.26, and the specific growth rate (SGR) was 1.39 and 0.10 % day-1 in T1 and T2 respectively. In both treatments 100% fish were survived and provided the net production (kg/ha) 2807.06 and 2557.78 in T1 and T2, respectively. The water quality parameters were within the suitable range for fish culture. Between the feeds evaluated, feed with 36.67% protein (T1) proved best result considering the growth and production performance of the fish. Overall growth performance of T. tor was satisfactory; however, further research is needed. J. Bangladesh Agril. Univ. 16(3): 533–538, December 2018